Finite Element Applications to Evaluate the Stress and Strain Field in the Vicinity of an Imperfection in Thin Shells - Karpiński, S. (Engineering Transactions, 1995)
The paper presents the method of calculation of the mechanical and technological parameters of thin spherical shells loaded by internal pressure. The FEM and the plasticity law of the material are introduced to the calculation. The deviations from the designed geometry of spherical shells may be due to fabrication and installation defects, and for that reason it is necessary to evaluate the level of stresses and the nature of the stress redistribution. Numerical results are presented on the diagrams to demonstrate the efficiency of the method and general conclusions are also given at the end of paper.